Impact of low-pressure pneumoperitoneum and deep neuromuscular blockade on surgeon satisfaction and patient outcomes in laparoscopic cholecystectomy patients: A prospective randomised controlled study - Alparslan Koç; Ufuk Memiş; Didem Onk; Talha Karataş; Mustafa Gazi; Ali Caner Sayar; Muhammet Ali Arı (Journal of Minimal Access Surgery)
Introduction: The impact of laparoscopic surgery on homeostatic systems necessitates careful consideration of intra-abdominal pressure (IAP) management. This study investigated the effects of low-pressure pneumoperitoneum with deep neuromuscular blockade (NMB) on surgeon satisfaction, haemodynamics and post-operative outcomes in laparoscopic cholecystectomy patients. Patients and Methods: The study design involves prospective randomised control. Ninety patients were assigned to low (7–10 mmHg, n = 45) or normal (12–16 mmHg, n = 45) IAP groups. Deep NMB, guided by train-of-four monitoring, was administered. This study evaluated surgical rating scale scores, haemodynamics and post-operative outcomes through a literature review. A computer programme (IBM, SPSS) was used for statistical analysis. Chi-square and Mann-Whitney U tests were used to analyse patients’ IAP levels, additional NMB requirements, surgical rating scale scores and numerical rating scales. Patient demographics and other intraoperative and post-operative variables were analysed with Student’s t-test and the Mann-Whitney U test. Values of P < 0.05 were considered to indicate statistical significance. Results: No significant demographic differences were observed. The low-pressure group exhibited lower post-operative pain (P < 0.01) and reduced analgesia requirements (P = 0.00). On analysis of the surgeon rating scale, no disparities were evident between the groups. NMB usage correlated with height and weight (P < 0.01). Heart rate showed no intergroup differences. The MAP measured after 15 min was lower in Group L, and the difference was significant (P = 0.023). The SAP measured after 30 min was lower in Group L, and the difference was significant (P = 0.017). Blood gas values and surgical field visibility were unaffected by the IAP. The positive correlations between NMB, height and weight aligned with previous research. Conclusion: This study highlights successful laparoscopic cholecystectomy under low IAP, deep NMB and favourable post-operative outcomes. Despite these limitations, the findings contribute to optimising laparoscopic surgical approaches.